Control method for dendritic structure of multi-principal-element rare earth doped zirconium oxide thermal barrier coating
The dendritic structure of multi-main rare earth doped zirconia thermal barrier coating is regulated through liquid plasma electrolysis technology, which solves the problem of preparing long-life thermal barrier coatings on surfaces of complex components of aero engines, and significantly improves the thermal cycle life and thermal insulation temperature of the coating.
Patent Information
- Application Number
- CN202411728269.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-28
AI Technical Summary
It is difficult to prepare long-life, high-reliability thermal barrier coatings on the surface of complex components of aircraft engines in the prior art, and the thermal barrier coatings with traditional hierarchical structures and column crystal structures have limited thermal impact resistance. YSZ materials are prone to phase change at 1200°C and have poor thermal insulation performance.
Through liquid plasma electrolysis technology, the dendritic structure of multi-main rare earth doped zirconia thermal barrier coating is regulated, and the doping high-entropy strategy of multi-main rare earth is used to reduce phonon scattering, and the strain tolerance of the coating is improved through dendritic structures of appropriate size and morphology.
It significantly improves the thermal cycle life and insulation temperature of the thermal barrier coating, enhances the thermal impact performance of the coating, and is suitable for the preparation of inner and outer surface coatings of complex shape workpieces.
Smart Images

Figure HDA0005159710280000011 
Figure HDA0005159710280000021 
Figure HDA0005159710280000022
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of thermal barrier coatings, and in particular relates to a method for preparing a thermal barrier coating, and in particular relates to a method for controlling a dendritic structure of a multi-principal rare earth-doped zirconia thermal barrier coating. Background Art
[0002] Thermal barrier coatings are commonly used on the surface of high-temperature hot end components. They are a coating system with surface protection functions and good heat insulation effects. They are mainly used to reduce the operating temperature of the substrate and protect it from corrosion, wear, and high-temperature oxidation. Preparing thermal barrier coatings on the hot end components of high-temperature engines can not only reduce fuel consumption, improve efficiency, and extend the service life of hot end components, but also improve the substrate's resistance to high-temperature corrosion and increase the engine's operating temperature.
[0003] At present, the main methods for preparing thermal barrier coatings include plasma spraying and electron beam-physical vapor deposition. Plasma spraying is to generate a plasma flame flow through a plasma spray gun, heat and melt the coating material, atomize it through a high-speed airflow and spray it onto the surface of the substrate at a very high speed to form a coating. Its composition can be controlled artificially, and the production efficiency is high, but the prepared coating has a layered structure with pores and holes, and its thermal shock resistance is limited. Electron beam-physical vapor deposition is that after the vacuum chamber of the equipment reaches a certain vacuum requirement, the electron gun starts to emit an electron beam, directly irradiates the pre-evaporated material, heats and vaporizes the material, and the material vapor is deposited on the substrate in the form of atoms or molecules to form a coating. This technical equipment is expensive, has high manufacturing costs, and needs to be carried out under vacuum, so it is not easy to deposit large-area samples. In addition, these methods are difficult to prepare thermal barrier coatings on the surface and inner cavity of complex-shaped workpieces.
[0004] Liquid phase plasma electrolysis technology is a new technology developed on the basis of anodic oxidation to grow thermal barrier coatings on metal surfaces. According to the different positive and negative poles of the sample connected to the power supply, it is mainly divided into two categories: anodic liquid phase plasma electrolysis technology and cathodic liquid phase plasma electrolysis technology. One of the great advantages of this technology is that it can prepare coatings on complex surfaces and inner cavities. Anodic liquid phase plasma electrolytic oxidation technology is also commonly known as "micro-arc oxidation". It uses valve metals such as Al, Mg, Ti and their alloys as anodes, but it is only applicable to valve metals and cannot be used for non-valve metal high-temperature alloys.
[0005] The existing technology has the problems that the process for preparing thermal barrier coatings on the surface of aircraft engines is complicated, the required equipment is expensive, the thermal shock resistance is limited, and it is difficult to prepare long-life thermal barrier coatings on the inner surface of complex parts. Summary of the invention
[0006] The purpose of the present invention is, on the one hand, to solve the problem that it is difficult to prepare long-life, high-reliability thermal barrier coatings on the surface of complex parts of aircraft engines in the prior art. On the other hand, it solves the problem that the thermal barrier coatings with traditional hierarchical structures and columnar crystal structures have limited thermal shock resistance, the YSZ material is prone to phase change at 1200°C, and has poor thermal insulation performance. Through liquid plasma electrolysis technology, the dendritic structure of multi-principal rare earth-doped zirconia thermal barrier coatings is regulated to improve the high reliability of thermal barrier coatings on the surface of complex parts. Among them, the high entropy strategy of doping multi-principal rare earths reduces phonon scattering and increases the thermal insulation temperature of the thermal barrier coating, while the dendritic structure of suitable size and shape can significantly improve the strain tolerance of the coating, thereby improving the thermal cycle life of the coating.
[0007] In order to achieve the above objectives, the present invention adopts the following technical solutions to achieve the above objectives:
[0008] A method for controlling a dendritic structure of a multi-principal rare earth doped zirconium oxide thermal barrier coating comprises the following steps:
[0009] A high-temperature alloy sample with a bonding layer is placed in a first electrolyte, and the high-temperature alloy sample is used as a negative electrode and a graphite plate is used as a positive electrode. A micro-arc oxidation power supply is connected to perform a first electrolysis, and an anti-oxidation ceramic barrier layer is deposited on the surface of the high-temperature alloy sample. Then, the high-temperature alloy sample with the anti-oxidation ceramic barrier layer is placed in a second electrolyte, and the high-temperature alloy sample is used as a negative electrode and a graphite plate is used as a positive electrode. A micro-arc oxidation power supply is connected to perform a second electrolysis, and a multi-principal rare earth doped zirconia thermal barrier coating with a dendritic structure is obtained; wherein the first electrolyte includes aluminum nitrate and rare earth element metal salts, and the second electrolyte includes zirconium nitrate and rare earth element metal salts.
[0010] Furthermore, in the first electrolyte, the concentration of aluminum nitrate is 0.1-1 mol / L, the concentration of the rare earth element metal salt is 0.01-0.5 mol / L, and the rare earth element metal salt is one of yttrium nitrate, cerium nitrate, scandium nitrate, ytterbium nitrate, gadolinium nitrate and lanthanum nitrate.
[0011] Furthermore, in the second electrolyte, the concentration of zirconium nitrate is 0.1-1 mol / L, the concentration of rare earth metal salt is 0.01-0.5 mol / L, and two or more of yttrium nitrate, cerium nitrate, scandium nitrate, ytterbium nitrate, gadolinium nitrate and lanthanum nitrate are contained.
[0012] Furthermore, the solvent in the first electrolysis and the second electrolysis is a mixture of ethanol and water.
[0013] Furthermore, the rare earth element metal salts in the first electrolyte and the second electrolyte are two or more of yttrium nitrate, cerium nitrate, scandium nitrate, ytterbium nitrate, gadolinium nitrate and lanthanum nitrate.
[0014] Furthermore, the conditions of the first electrolysis and the second electrolysis are: pulse voltage of 200-500V, operating frequency of 100-1000Hz, duty cycle of 5-30%, electrolysis temperature of 0-50°C, and time of 10-120min.
[0015] Furthermore, a high temperature alloy specimen with a bonding layer is prepared by the following process:
[0016] The surface of the high-temperature alloy sample is sandblasted, and then a wide-range high-energy plasma spraying method is adopted to spray on the surface of the high-temperature alloy sample to form a bonding layer, thereby obtaining a high-temperature alloy sample with a bonding layer.
[0017] Furthermore, the thickness of the adhesive layer is 50 to 150 μm.
[0018] Furthermore, the bonding layer is made of NiCrAlY, NiCoCrAlY or CoNiCrAlY.
[0019] Furthermore, the high-temperature alloy sample is an iron-based high-temperature alloy, a nickel-based high-temperature alloy or a cobalt-based high-temperature alloy.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention prepares a rare earth doped zirconium oxide thermal barrier coating by cathode liquid plasma electrolytic deposition technology. The porous cross-linked dendritic structure of the thermal barrier coating greatly improves the thermal cycle life of the thermal barrier coating, and can be applied to the field of surface thermal protection technology, specifically showing the following advantages:
[0022] 1) The whole process is carried out in the liquid phase environment of the electrolyte, and a thermal barrier coating of a certain thickness can be formed on the inner and outer surfaces of any complex-shaped workpiece, especially on the inner and outer surfaces of special-shaped parts.
[0023] 2) The present invention only requires that the base material be conductive, and therefore is applicable to all metals, and the base material has a wide range of applicability.
[0024] 3) The equipment required for the present invention is simple and the equipment cost is low. By adjusting the power supply parameters such as voltage, frequency, duty cycle and the composition of the electrolyte, the composition of the thermal barrier coating can be controlled, and the coating structure such as pores and thickness can be adjusted. The process is simple and does not require harsh conditions such as atmosphere protection and high temperature.
[0025] 4) The generation of plasma and its participation in the workpiece surface during the treatment process, with its high energy density characteristics, causes the deposits on the workpiece surface to discharge and sinter to form a thermal barrier coating. During the discharge, plasma breakdown occurs at the weak part of the coating, and its high temperature causes the coating to melt and splash outward, and it quickly solidifies under the quenching action of the electrolyte to form a porous cross-linked dendritic structure. The rich pore defects in this porous cross-linked dendritic structure can effectively reduce the phonon thermal conductivity, which is beneficial to the reduction of the thermal conductivity of the thermal barrier coating, thereby increasing the thermal insulation temperature of the coating. The vertical crack-like defects inside the structure can improve the strain tolerance of the coating under thermal load to a certain extent, effectively improving the thermal cycle life of the coating.
[0026] 5) The multi-principal rare earth doped zirconia coating material system forms a mesoscopic defect structure in which the lattice atoms are highly disordered, resulting in severe phonon-grain boundary scattering, which is beneficial to the reduction of the thermal conductivity of the thermal barrier coating and improves the thermal insulation temperature of the coating at the mesoscopic level.
[0027] 6) Pre-deposition of rare earth doped anti-oxidation ceramic layer can effectively induce uniform plasma discharge, thereby improving the uniformity and density of ceramic coating deposition in the thermal barrier coating system. In addition, the rare earth doped anti-oxidation layer can also effectively alleviate the thermal expansion mismatch between the bonding layer and the ceramic layer, thereby improving the protective performance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The cross-sectional SEM images of the thermal barrier coating prepared in Example 1 of the present invention, wherein: (a) a ZrO2 coating with a duty cycle of 10%; (b) a ZrO2 coating with a duty cycle of 20%; (c) a YSZ coating; (d) a 5% Ce-doped YSZ thermal barrier coating; (e) a 10% Ce-doped YSZ thermal barrier coating; (f) a 20% Ce-doped YSZ thermal barrier coating; (g) an aluminum oxide layer composited with a 10% Ce-doped YSZ thermal barrier coating; (h) an aluminum oxide layer composited with a 20% Ce-doped YSZ thermal barrier coating; (i) a rare earth-doped ZrCeGdYO2 thermal barrier coating; (j) a rare earth-doped ZrCeGdYO2 thermal barrier coating after adding a barrier layer;
[0029] Figure 2 XRD phase analysis results of the rare earth element Ce doped YSZ thermal barrier coating prepared in Example 1 of the present invention;
[0030] Figure 3 The thermal insulation temperature of the thermal barrier coating prepared in Example 1 of the present invention per 100 μm thickness, wherein (a) is a CeYSZ coating; (b) is a Ce-doped YSZ thermal barrier coating after adding an anti-oxidation barrier layer;
[0031] Figure 4Surface images of the thermal barrier coatings prepared in Example 1 of the present invention at different thermal shock cycle numbers, where (a) is the YSZ coating, which is 20 cycles, 40 cycles and 58 cycles from left to right; (b) is the Ce-doped YSZ thermal barrier coating, which is 50 cycles, 98 cycles and 105 cycles from left to right; (c) is the Ce-doped YSZ thermal barrier coating after adding an antioxidant barrier layer, which is 270 cycles, 350 cycles and 450 cycles from left to right. DETAILED DESCRIPTION
[0032] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.
[0033] The control method of the dendritic structure of a multi-principal rare earth doped zirconia thermal barrier coating of the present invention includes two control strategies: one is to directly deposit a multi-principal rare earth doped ceramic layer on the sprayed bonding layer, and the other is to prefabricate an anti-oxidation barrier layer on the sprayed bonding layer and then continue to deposit the ceramic layer. For the first strategy, a bonding layer is sprayed on the surface of the high-temperature alloy sample by a wide-speed high-energy plasma spraying technology; then the high-temperature alloy sample of the bonding layer is placed in an electrolyte to deposit a multi-principal rare earth doped ceramic layer. The specific process is to connect a pulse power supply, with the high-temperature alloy sample as the negative electrode and the graphite plate as the positive electrode, and electrolyze in an electrolyte at 0 to 50°C for 10 to 120 minutes under the conditions of a pulse voltage of 200 to 500V, an operating frequency of 100 to 1000Hz, and a duty cycle of 5 to 30%; for the second strategy, an anti-oxidation ceramic barrier layer is first deposited on the surface of the high-temperature alloy of the bonding layer by the above technology, and then a multi-principal rare earth doped coating is deposited. The equipment used in the present invention is simple and the process parameters are easy to adjust. The doping of rare earth elements and the introduction of an anti-oxidation barrier layer effectively improve the density of the dendritic structure coating, resulting in an improvement in its thermal insulation temperature and thermal shock performance.
[0034] The control method of the present invention specifically comprises the following steps:
[0035] (1) Surface pretreatment of the high-temperature alloy sample: The surface of the high-temperature alloy sample is sandblasted, and a NiCrAlY, NiCoCrAlY or CoNiCrAlY bonding layer with a thickness of 50 to 150 μm is sprayed on the surface by a wide-range high-energy plasma spraying method to obtain a high-temperature alloy sample with a bonding layer; wherein the high-temperature alloy sample is an iron-based high-temperature alloy, a nickel-based high-temperature alloy or a cobalt-based high-temperature alloy.
[0036] (2) preparing the electrolyte: using an ethanol solution containing 10 to 50% water by volume as the solvent;
[0037] Aluminum nitrate and rare earth metal salt are added to a solvent to prepare a first electrolyte, wherein the concentration of aluminum nitrate is 0.1-1 mol / L, the concentration of rare earth metal salt is 0.01-0.5 mol / L, and the concentration of rare earth metal salt is determined according to the concentration of zirconium nitrate. The rare earth metal salt is one of yttrium nitrate, cerium nitrate, scandium nitrate, ytterbium nitrate, gadolinium nitrate and lanthanum nitrate.
[0038] Zirconium nitrate and rare earth metal salt are added to a solvent to prepare a second electrolyte, wherein the concentration of zirconium nitrate in the second electrolyte is 0.1-1 mol / L, and the concentration of the rare earth metal salt is determined according to the concentration of zirconium nitrate. The rare earth metal salt is two or more of yttrium nitrate, cerium nitrate, scandium nitrate, ytterbium nitrate, gadolinium nitrate and lanthanum nitrate. The concentration of each rare earth metal salt is 0.01-0.5 mol / L.
[0039] (3) Preparation of rare earth element doped zirconium oxide thermal barrier coating: The high-temperature alloy sample with a bonding layer prepared in step (1) is placed in a first electrolyte, with the high-temperature alloy sample as the negative electrode and the graphite plate as the positive electrode, connected to a micro-arc oxidation power supply, and electrolyzed in an electrolyte at 0 to 50°C for 10 to 120 minutes under the conditions of a pulse voltage of 200 to 500 V, an operating frequency of 100 to 1000 Hz, and a duty cycle of 5 to 30%, to deposit an antioxidant ceramic barrier layer. After the deposition is completed, the sample is placed in a second electrolyte, with the high-temperature alloy sample as the negative electrode and the graphite plate as the positive electrode, connected to a micro-arc oxidation power supply, and electrolyzed in an electrolyte at 0 to 50°C for 10 to 120 minutes under the conditions of a pulse voltage of 200 to 500 V, an operating frequency of 100 to 1000 Hz, and a duty cycle of 5 to 30%. After the deposition is completed, the high-temperature alloy sample is rinsed with deionized water and placed in an oven for drying, thereby obtaining a multi-principal rare earth doped zirconium oxide thermal barrier coating dendritic structure, in which ZrO2 is a t' tetragonal phase.
[0040] The rare earth doped zirconia thermal barrier coating prepared by the present invention has a porous cross-linked dendritic structure. With the increase of rare earth element content, the structure close to the substrate is relatively denser; with the introduction of the anti-oxidation barrier layer, the size of the dendritic structure decreases and the density of the coating increases. And the thermal insulation temperature of the rare earth doped zirconia thermal barrier coating with a thickness of 100 μm is 40-80°C.
[0041] Under the thermal shock conditions of rapidly heating to 1300°C in 10-30s, keeping warm for 5-8min, and then rapidly air cooling to room temperature in 10-30s, the number of thermal cycles of the rare earth doped zirconia thermal barrier coating is 300-800 times.
[0042] Example 1
[0043] (1) Surface pretreatment of high-temperature alloy specimens: The surface of the GH4169 high-temperature alloy specimen was sandblasted, and a NiCrAlY bonding layer with a thickness of 100 μm was sprayed on its surface using a wide-range high-energy plasma spraying technology.
[0044] (2) Preparation of electrolyte: Two solutions were prepared using an ethanol solution containing 30% water by volume as a solvent. Aluminum nitrate and yttrium nitrate were added to the solvent to prepare a first electrolyte. In the first electrolyte, the concentration of aluminum nitrate was 0.5 mol / L, and the concentration of yttrium nitrate was 0.10 mol / L.
[0045] Zirconium nitrate, yttrium nitrate and cerium nitrate are added to a solvent to prepare a second electrolyte, wherein the concentration of zirconium nitrate is 0.5 mol / L, the concentration of cerium nitrate is 0.10 mol / L and the concentration of yttrium nitrate is 0.10 mol / L.
[0046] (3) Preparation of rare earth element doped zirconium oxide thermal barrier coating: The GH4169 high temperature alloy sample with bonding layer prepared in step (1) is placed in the first electrolyte, with the high temperature alloy sample as the negative electrode and the graphite plate as the positive electrode, connected to a micro-arc oxidation power supply, and electrolyzed in the electrolyte at 40°C for 30 minutes under the conditions of pulse voltage of 300V, working frequency of 500Hz, and duty cycle of 10%. After the deposition is completed, it is placed in the second electrolyte, with the high temperature alloy sample as the negative electrode and the graphite plate as the positive electrode, connected to a micro-arc oxidation power supply, and electrolyzed in the electrolyte at 40°C for 30 minutes under the conditions of pulse voltage of 300V, working frequency of 500Hz, and duty cycle of 10%. After the deposition is completed, the high temperature alloy sample is rinsed with deionized water, placed in an oven for drying, and a rare earth element doped zirconium oxide thermal barrier coating is formed on the surface of the sample.
[0047] The coating was subjected to 1200℃ insulation temperature and 1300℃ thermal shock tests. Figure 2 It can be seen that the insulation temperature of the coating is 52°C per 100 μm thickness.
[0048] The coating surface after different cycles is as follows Figure 4 As shown in (c), the thermal shock life of the coating reaches 450 times, which is nearly eight times higher than the thermal shock life of 58 times of the YSZ thermal barrier coating, indicating that the addition of an antioxidant barrier layer greatly improves the thermal shock performance of the coating.
[0049] Example 2
[0050] (1) Surface pretreatment of high-temperature alloy specimens: The surface of the GH4169 high-temperature alloy specimen was sandblasted, and a NiCrAlY bonding layer with a thickness of 100 μm was sprayed on its surface using a wide-range high-energy plasma spraying technology.
[0051] (2) Preparation of electrolyte: Two solutions were prepared using an ethanol solution containing 30% water by volume as a solvent. Aluminum nitrate and yttrium nitrate were added to the solvent to prepare a first electrolyte. In the first electrolyte, the concentration of aluminum nitrate was 0.5 mol / L, and the concentration of yttrium nitrate was 0.20 mol / L.
[0052] Zirconium nitrate, yttrium nitrate and cerium nitrate are added to a solvent to prepare a second electrolyte, wherein the concentration of zirconium nitrate is 0.5 mol / L, the concentration of cerium nitrate is 0.20 mol / L and the concentration of yttrium nitrate is 0.20 mol / L.
[0053] (3) Preparation of rare earth element doped zirconium oxide thermal barrier coating: The GH4169 high temperature alloy sample with bonding layer prepared in step (1) is placed in the first electrolyte, with the high temperature alloy sample as the negative electrode and the graphite plate as the positive electrode, connected to a micro-arc oxidation power supply, and electrolyzed in the electrolyte at 30°C for 60 minutes under the conditions of pulse voltage of 200V, working frequency of 500Hz, and duty cycle of 10%. After the deposition is completed, it is placed in the second electrolyte, with the high temperature alloy sample as the negative electrode and the graphite plate as the positive electrode, connected to a micro-arc oxidation power supply, and electrolyzed in the electrolyte at 30°C for 60 minutes under the conditions of pulse voltage of 200V, working frequency of 500Hz, and duty cycle of 10%. After the deposition is completed, the high temperature alloy sample is rinsed with deionized water and placed in an oven for drying to form a rare earth element doped zirconium oxide thermal barrier coating on the surface of the sample.
[0054] from Figure 1 It can be seen in (h) that, compared with Example 1, as the rare earth element content continues to increase, the number of electrolyte cations increases, the content of hydroxide formed increases, and the coating thickness increases. The density of the coating is further improved near the substrate, showing a dendritic structure with circular pores cross-linked.
[0055] Example 3
[0056] (1) Surface pretreatment of high-temperature alloy samples: The surface of the GH4169 high-temperature alloy sample was sandblasted, and a NiCrAlY bonding layer with a thickness of 150 μm was sprayed on its surface using a wide-range high-energy plasma spraying technology.
[0057] (2) Preparation of electrolyte: Two solutions were prepared using an ethanol solution containing 30% water by volume as a solvent. Aluminum nitrate and yttrium nitrate were added to the solvent to prepare a first electrolyte. In the first electrolyte, the concentration of aluminum nitrate was 0.5 mol / L, and the concentration of yttrium nitrate was 0.20 mol / L. Zirconium nitrate, yttrium nitrate, cerium nitrate, and gadolinium nitrate were added to the solvent to prepare a second electrolyte. In the second electrolyte, the concentration of zirconium nitrate was 1 mol / L, the concentration of cerium nitrate was 0.10 mol / L, the concentration of yttrium nitrate was 0.10 mol / L, and the concentration of gadolinium nitrate was 0.10 mol / L.
[0058] (3) Preparation of rare earth element doped zirconium oxide thermal barrier coating: The GH4169 high temperature alloy sample with bonding layer prepared in step (1) is placed in the first electrolyte, with the high temperature alloy sample as the negative electrode and the graphite plate as the positive electrode, connected to a micro-arc oxidation power supply, and electrolyzed in a 50°C electrolyte for 10 minutes under the conditions of a pulse voltage of 500V, an operating frequency of 1000Hz, and a duty cycle of 30%. After the deposition is completed, a ceramic barrier layer is formed, and then placed in a second electrolyte, with the high temperature alloy sample as the negative electrode and the graphite plate as the positive electrode, connected to a micro-arc oxidation power supply, and electrolyzed in a 40°C electrolyte for 30 minutes under the conditions of a pulse voltage of 300V, an operating frequency of 500Hz, and a duty cycle of 10%. After the deposition is completed, the high temperature alloy sample is rinsed with deionized water, placed in an oven for drying, and a rare earth element doped YSZ thermal barrier coating is formed on the surface of the sample.
[0059] from Figure 1 It can be seen in (j) that after adding the barrier layer, the cross-sectional dendritic size of the multi-principal rare earth doped coating is reduced and the longitudinal crack defects are increased, which is a dendritic structure with cross-linked longitudinal cracks.
[0060] Example 4
[0061] (1) Surface pretreatment of high-temperature alloy samples: The surface of the GH4169 high-temperature alloy sample was sandblasted, and a NiCoCrAlY bonding layer with a thickness of 150 μm was sprayed on its surface by wide-range high-energy plasma spraying.
[0062] (2) Preparation of electrolyte: Two solutions were prepared using an ethanol solution containing 30% water by volume as a solvent. Aluminum nitrate and yttrium nitrate were added to the solvent to prepare a first electrolyte. In the first electrolyte, the concentration of aluminum nitrate was 0.5 mol / L, and the concentration of yttrium nitrate was 0.20 mol / L. Zirconium nitrate, yttrium nitrate, cerium nitrate, and gadolinium nitrate were added to the solvent to prepare a second electrolyte. In the second electrolyte, the concentration of zirconium nitrate was 1 mol / L, the concentration of cerium nitrate was 0.10 mol / L, the concentration of yttrium nitrate was 0.10 mol / L, and the concentration of gadolinium nitrate was 0.10 mol / L.
[0063] (3) Preparation of rare earth element doped zirconium oxide thermal barrier coating: The GH4169 high temperature alloy sample with bonding layer prepared in step (1) is placed in the first electrolyte, with the high temperature alloy sample as the negative electrode and the graphite plate as the positive electrode, connected to a micro-arc oxidation power supply, and electrolyzed in the electrolyte at 30°C for 120 minutes under the conditions of pulse voltage of 300V, working frequency of 500Hz, and duty cycle of 10%. After the deposition is completed, it is placed in the second electrolyte, with the high temperature alloy sample as the negative electrode and the graphite plate as the positive electrode, connected to a micro-arc oxidation power supply, and electrolyzed in the electrolyte at 40°C for 30 minutes under the conditions of pulse voltage of 300V, working frequency of 500Hz, and duty cycle of 10%. After the deposition is completed, the high temperature alloy sample is rinsed with deionized water, placed in an oven for drying, and a rare earth element doped YSZ thermal barrier coating is formed on the surface of the sample.
[0064] Example 5
[0065] (1) Surface pretreatment of high-temperature alloy samples: The surface of the iron-based high-temperature alloy sample was sandblasted, and a CoNiCrAlY bonding layer with a thickness of 100 μm was sprayed on the surface by a wide-range high-energy plasma spraying method.
[0066] (2) Preparation of electrolyte: Two solutions were prepared using an ethanol solution containing 10% water by volume as the solvent. Aluminum nitrate and yttrium nitrate were added to the solvent to prepare a first electrolyte. In the first electrolyte, the concentration of aluminum nitrate was 0.1 mol / L, and the concentration of yttrium nitrate was 0.01 mol / L. Zirconium nitrate, scandium nitrate, and lanthanum nitrate were added to the solvent to prepare a second electrolyte. In the second electrolyte, the concentration of zirconium nitrate was 1 mol / L, the concentration of scandium nitrate was 0.01 mol / L, and the concentration of lanthanum nitrate was 0.5 mol / L.
[0067] (3) Preparation of rare earth element doped zirconium oxide thermal barrier coating: The GH4169 high temperature alloy sample with bonding layer prepared in step (1) is placed in the first electrolyte, with the high temperature alloy sample as the negative electrode and the graphite plate as the positive electrode, connected to a micro-arc oxidation power supply, and electrolyzed in the electrolyte at 0°C for 60 minutes under the conditions of pulse voltage of 200V, working frequency of 100Hz, and duty cycle of 5%. After the deposition is completed, it is placed in the second electrolyte, with the high temperature alloy sample as the negative electrode and the graphite plate as the positive electrode, connected to a micro-arc oxidation power supply, and electrolyzed in the electrolyte at 40°C for 30 minutes under the conditions of pulse voltage of 100V, working frequency of 700Hz, and duty cycle of 20%. After the deposition is completed, the high temperature alloy sample is rinsed with deionized water, placed in an oven for drying, and a rare earth element doped zirconium oxide thermal barrier coating is formed on the surface of the sample.
[0068] Example 6
[0069] (1) Surface pretreatment of high-temperature alloy samples: The surface of the cobalt-based high-temperature alloy sample was sandblasted, and a NiCoCrAlY bonding layer with a thickness of 50 μm was sprayed on the surface by plasma spraying.
[0070] (2) Preparation of electrolyte: Two solutions are prepared using an ethanol solution containing 50% water by volume as a solvent. Aluminum nitrate and yttrium nitrate are added to the solvent to prepare a first electrolyte. In the first electrolyte, the concentration of aluminum nitrate is 1 mol / L, and the concentration of yttrium nitrate is 0.50 mol / L. Zirconium nitrate, yttrium nitrate, cerium nitrate and gadolinium nitrate are added to the solvent to prepare a second electrolyte. In the second electrolyte, the concentration of zirconium nitrate is 0.1 mol / L, the concentration of cerium nitrate is 0.20 mol / L, the concentration of yttrium nitrate is 0.30 mol / L, and the concentration of gadolinium nitrate is 0.50 mol / L.
[0071] (3) Preparation of rare earth element doped zirconium oxide thermal barrier coating: The GH4169 high temperature alloy sample with bonding layer prepared in step (1) is placed in the first electrolyte, with the high temperature alloy sample as the negative electrode and the graphite plate as the positive electrode, connected to a micro-arc oxidation power supply, and electrolyzed in the electrolyte at 30°C for 30 minutes under the conditions of pulse voltage of 400V, working frequency of 1000Hz, and duty cycle of 20%. After the deposition is completed, it is placed in the second electrolyte, with the high temperature alloy sample as the negative electrode and the graphite plate as the positive electrode, connected to a micro-arc oxidation power supply, and electrolyzed in the electrolyte at 40°C for 100 minutes under the conditions of pulse voltage of 400V, working frequency of 500Hz, and duty cycle of 10%. After the deposition is completed, the high temperature alloy sample is rinsed with deionized water, placed in an oven for drying, and a rare earth element doped YSZ thermal barrier coating is formed on the surface of the sample.
[0072] Comparative Example 1
[0073] (1) Surface pretreatment of high-temperature alloy specimens: The surface of the GH4169 high-temperature alloy specimen was sandblasted, and a NiCrAlY bonding layer with a thickness of 100 μm was sprayed on its surface using a wide-range high-energy plasma spraying technology.
[0074] (2) Preparation of electrolyte: Using an ethanol solution containing 30% water by volume as a solvent, zirconium nitrate is added to the solvent to prepare an electrolyte, wherein the concentration of zirconium nitrate in the electrolyte is 0.5 mol / L.
[0075] (3) Preparation of zirconium oxide thermal barrier coating: The GH4169 high temperature alloy sample with a bonding layer prepared in step (1) was placed in an electrolyte, with the high temperature alloy sample as the negative electrode and the graphite plate as the positive electrode, connected to a micro-arc oxidation power supply, and electrolyzed in an electrolyte at 40° C. for 30 minutes under the conditions of a pulse voltage of 300 V, an operating frequency of 500 Hz, and a duty cycle of 10%. After the deposition was completed, the high temperature alloy sample was rinsed with deionized water and placed in an oven for drying to form a zirconium oxide thermal barrier coating on the surface of the sample.
[0076] from Figure 1 As can be seen in (a), the coating presents a more dispersed dendritic porous structure.
[0077] from Figure 1 It can be seen in (g) that, compared with comparative example 1, the size of the dendritic structure of the coating is reduced after the prefabricated barrier layer, the density of the coating is increased, the cross-sectional thickness is uniform, and there are no holes vertically penetrating the coating. It is a dendritic structure with circular pores cross-linked.
[0078] Comparative Example 2
[0079] (1) Surface pretreatment of high-temperature alloy specimens: The surface of the GH4169 high-temperature alloy specimen was sandblasted, and a NiCrAlY bonding layer with a thickness of 100 μm was sprayed on its surface using a wide-range high-energy plasma spraying technology.
[0080] (2) Preparation of electrolyte: Using an ethanol solution containing 30% water by volume as a solvent, zirconium nitrate is added to the solvent to prepare an electrolyte, wherein the concentration of zirconium nitrate in the electrolyte is 0.5 mol / L.
[0081] (3) Preparation of zirconium oxide thermal barrier coating: The GH4169 high temperature alloy sample with a bonding layer prepared in step (1) was placed in an electrolyte, with the high temperature alloy sample as the negative electrode and the graphite plate as the positive electrode, connected to a micro-arc oxidation power supply, and electrolyzed in an electrolyte at 40° C. for 30 minutes under the conditions of a pulse voltage of 300 V, an operating frequency of 500 Hz, and a duty cycle of 20%. After the deposition was completed, the high temperature alloy sample was rinsed with deionized water and placed in an oven for drying to form a rare earth element doped zirconium oxide thermal barrier coating on the surface of the sample.
[0082] from Figure 1 As can be seen from (b), compared with comparative example 1, as the duty cycle increases, the duration of the voltage difference between the anode and cathode is increased, making Zr 4+ The time for ions to move toward the cathode is prolonged, and the increase in duty cycle also increases the duration of plasma discharge, causing the sintering transformation of Zr(OH)4 to ZrO2 coating, so the coating formation speed becomes faster and the coating thickness increases.
[0083] Comparative Example 3
[0084] (1) Surface pretreatment of high-temperature alloy specimens: The surface of the GH4169 high-temperature alloy specimen was sandblasted, and a NiCrAlY bonding layer with a thickness of 100 μm was sprayed on its surface using a wide-range high-energy plasma spraying technology.
[0085] (2) Preparation of electrolyte: Using an ethanol solution containing 30% water by volume as a solvent, zirconium nitrate, yttrium nitrate and cerium nitrate are added to the solvent to prepare an electrolyte, wherein the concentration of zirconium nitrate is 0.5 mol / L, the concentration of cerium nitrate is 0.05 mol / L, and the concentration of yttrium nitrate is 0.05 mol / L.
[0086] (3) Preparation of rare earth element doped zirconium oxide thermal barrier coating: The GH4169 high temperature alloy sample with bonding layer prepared in step (1) was placed in an electrolyte, with the high temperature alloy sample as the negative electrode and the graphite plate as the positive electrode, connected to a micro-arc oxidation power supply, and electrolyzed in an electrolyte at 40°C for 30 minutes under the conditions of a pulse voltage of 300V, an operating frequency of 500Hz, and a duty cycle of 10%. After the deposition was completed, the high temperature alloy sample was rinsed with deionized water and placed in an oven for drying to form a rare earth element doped zirconium oxide thermal barrier coating on the surface of the sample.
[0087] from Figure 1 It can be seen from (c) and (d) that compared with the zirconia coating structure, the YSZ coating has an increased thickness and longer dendrites. Further comparison revealed that the CeYSZ coating has a uniform cross-sectional thickness, and there are no holes penetrating the coating. The coating structure is dense near the substrate, and is a porous, cross-linked dendritic structure.
[0088] from Figure 2 It can be seen that the coating is entirely composed of t'-ZrO2 phase. Although yttrium and cerium nitrates were added to the electrolyte, the corresponding oxide components were not detected in the coating, indicating that yttrium and cerium elements were successfully doped into the ZrO2 lattice. In addition, there is no bonding layer phase in the XRD spectrum, indicating that the coating is thick and X-rays cannot penetrate the coating. A metallurgical bond is formed between the coating and the bonding layer, and the bonding strength is better.
[0089] The coating was subjected to 1200℃ insulation temperature and 1300℃ thermal shock tests. Figure 3 It can be seen that the thermal insulation temperature of the coating is 40°C at every 100 μm thickness. Figure 4 As shown in (a), (b) and (c), the thermal shock life of the coating reaches 105 times, which is nearly twice the thermal shock life of 58 times of the YSZ thermal barrier coating, indicating that the doping of Ce element greatly improves the performance of the coating.
[0090] Comparative Example 4
[0091] (1) Surface pretreatment of high-temperature alloy specimens: The surface of the GH4169 high-temperature alloy specimen was sandblasted, and a NiCrAlY bonding layer with a thickness of 100 μm was sprayed on its surface using a wide-range high-energy plasma spraying technology.
[0092] (2) Preparation of electrolyte: Using ethanol solution containing 30% water by volume as solvent, zirconium nitrate, yttrium nitrate and cerium nitrate are added to the solvent to prepare an electrolyte, wherein the concentration of zirconium nitrate is 0.5 mol / L, the concentration of cerium nitrate is 0.10 mol / L, and the concentration of yttrium nitrate is 0.10 mol / L.
[0093] (3) Preparation of rare earth element doped zirconium oxide thermal barrier coating: The GH4169 high temperature alloy sample with bonding layer prepared in step (1) was placed in an electrolyte, with the high temperature alloy sample as the negative electrode and the graphite plate as the positive electrode, connected to a micro-arc oxidation power supply, and electrolyzed in an electrolyte at 30°C for 60 minutes under the conditions of a pulse voltage of 200V, an operating frequency of 500Hz, and a duty cycle of 10%. After the deposition was completed, the high temperature alloy sample was rinsed with deionized water and placed in an oven for drying to form a rare earth element doped zirconium oxide thermal barrier coating on the surface of the sample.
[0094] from Figure 1 It can be seen in (e) that, compared with Comparative Example 3, as the voltage is reduced during the preparation of the coating, the density of the coating close to the substrate is further improved, and no cracks are observed between the coating and the bonding layer.
[0095] Comparative Example 5
[0096] (1) Surface pretreatment of high-temperature alloy samples: The surface of the GH4169 high-temperature alloy sample was sandblasted, and a NiCrAlY bonding layer with a thickness of 150 μm was sprayed on its surface using a wide-range high-energy plasma spraying technology.
[0097] (2) Preparation of electrolyte: Using ethanol solution containing 30% water by volume as solvent, zirconium nitrate, yttrium nitrate and cerium nitrate are added to the solvent to prepare an electrolyte, wherein the concentration of zirconium nitrate is 0.5 mol / L, the concentration of cerium nitrate is 0.20 mol / L, and the concentration of yttrium nitrate is 0.20 mol / L.
[0098] (3) Preparation of rare earth element doped zirconium oxide thermal barrier coating: The GH4169 high temperature alloy sample with bonding layer prepared in step (1) was placed in an electrolyte, with the high temperature alloy sample as the negative electrode and the graphite plate as the positive electrode, connected to a micro-arc oxidation power supply, and electrolyzed in an electrolyte at 40°C for 30 minutes under the conditions of a pulse voltage of 300V, an operating frequency of 500Hz, and a duty cycle of 10%. After the deposition was completed, the high temperature alloy sample was rinsed with deionized water and placed in an oven for drying to form a rare earth element doped zirconium oxide thermal barrier coating on the surface of the sample.
[0099] from Figure 1 As can be seen in (f), the coating cross-section thickness is uniform, the overall structure is dense, and there are no longitudinal defects. It is a porous cross-linked dendritic structure.
[0100] Comparative Example 6
[0101] (1) Surface pretreatment of high-temperature alloy samples: The surface of the GH4169 high-temperature alloy sample was sandblasted, and a NiCrAlY bonding layer with a thickness of 150 μm was sprayed on its surface using a wide-range high-energy plasma spraying technology.
[0102] (2) preparing an electrolyte: using an ethanol solution containing 50% water by volume as a solvent, adding zirconium nitrate, yttrium nitrate, cerium nitrate and gadolinium nitrate into the solvent to prepare an electrolyte, wherein the concentration of zirconium nitrate is 1 mol / L, the concentration of cerium nitrate is 0.10 mol / L, the concentration of yttrium nitrate is 0.10 mol / L, and the concentration of gadolinium nitrate is 0.10 mol / L.
[0103] (3) Preparation of rare earth element doped zirconium oxide thermal barrier coating: The GH4169 high temperature alloy sample with bonding layer prepared in step (1) was placed in an electrolyte, with the high temperature alloy sample as the negative electrode and the graphite plate as the positive electrode, connected to a micro-arc oxidation power supply, and electrolyzed in an electrolyte at 20° C. for 60 minutes under the conditions of a pulse voltage of 200 V, an operating frequency of 500 Hz, and a duty cycle of 20%. After the deposition was completed, the high temperature alloy sample was rinsed with deionized water and placed in an oven for drying to form a rare earth element doped YSZ thermal barrier coating on the surface of the sample.
[0104] from Figure 1 As can be seen in (i), the longitudinal defects in the coating cross section are reduced, and it is a porous cross-linked structure.
[0105] From the comparison between comparative examples 1-6 and examples 1-6, it can be seen that in the present invention, since the cathode liquid phase plasma electrolysis technology uses the metal to be treated as the cathode, the generation of plasma and the participation in the workpiece surface during the treatment process have the characteristics of high energy density, so that the deposits on the surface of the workpiece are discharged and sintered to form a thermal barrier coating, so the limitation of the substrate material can be broken, and a metal or ceramic coating can still be obtained on a non-valve metal. Since plasma participates in the formation process of the thermal barrier coating, during discharge, plasma breakdown occurs at the weak part of the coating, and its high temperature causes the coating at this place to melt and splash outward, and it quickly solidifies under the quenching action of the electrolyte to form a porous cross-linked dendritic structure, and gives the coating excellent performance.
[0106] The present invention provides a method for preparing a rare earth doped YSZ thermal barrier coating by cathode liquid phase plasma electrolytic deposition technology. The whole process of the method is carried out in a liquid phase environment of an electrolyte, so a coating can be formed on the inner and outer surfaces of any complex-shaped workpiece. Since only the base material is required to be conductive, it can be applied to all metals, and the base material has a wide applicability. The equipment only requires an ordinary micro-arc oxidation power supply, and the equipment cost is low. By adjusting the power supply parameters such as voltage, frequency, duty cycle and the composition of the electrolyte, the coating composition and structure can be controlled. The process is simple and does not require harsh conditions such as atmosphere protection and high temperature. During the processing, plasma will be generated and involved on the surface of the workpiece. The high energy density of the plasma causes the deposit on the surface of the workpiece to sinter to form a ceramic coating, and gives the coating excellent performance. The equipment used in the present invention is simple, the process parameters are easy to adjust, and the coating structure and thickness can be flexibly controlled.
[0107] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.
[0108] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
Claims
1. A method for controlling the dendritic structure of a multi-principal rare earth doped zirconia thermal barrier coating, characterized in that: The steps include: A high-temperature alloy sample with a bonding layer is placed in a first electrolyte, and the high-temperature alloy sample is used as a negative electrode and a graphite plate is used as a positive electrode. A micro-arc oxidation power supply is connected to perform a first electrolysis, and an anti-oxidation ceramic barrier layer is deposited on the surface of the high-temperature alloy sample. Then, the high-temperature alloy sample with the anti-oxidation ceramic barrier layer is placed in a second electrolyte, and the high-temperature alloy sample is used as a negative electrode and a graphite plate is used as a positive electrode. A micro-arc oxidation power supply is connected to perform a second electrolysis, and a multi-principal rare earth doped zirconia thermal barrier coating with a dendritic structure is obtained; wherein the first electrolyte includes aluminum nitrate and rare earth element metal salts, and the second electrolyte includes zirconium nitrate and rare earth element metal salts.
2. The control method of the dendritic structure of the multi-principal rare earth doped zirconia thermal barrier coating according to claim 1, characterized in that: In the first electrolyte, the concentration of aluminum nitrate is 0.1-1 mol / L, the concentration of the rare earth element metal salt is 0.01-0.5 mol / L, and the rare earth element metal salt is one of yttrium nitrate, cerium nitrate, scandium nitrate, ytterbium nitrate, gadolinium nitrate and lanthanum nitrate.
3. The control method of the dendritic structure of the multi-principal rare earth doped zirconia thermal barrier coating according to claim 1, characterized in that: In the second electrolyte, the concentration of zirconium nitrate is 0.1-1 mol / L, the concentration of rare earth metal salt is 0.01-0.5 mol / L, and two or more of yttrium nitrate, cerium nitrate, scandium nitrate, ytterbium nitrate, gadolinium nitrate and lanthanum nitrate are contained.
4. The method for controlling the dendritic structure of the multi-principal rare earth doped zirconia thermal barrier coating according to claim 1, characterized in that: The solvent in the first electrolysis and the second electrolysis is a mixture of ethanol and water.
5. The method for controlling the dendritic structure of the multi-principal rare earth doped zirconia thermal barrier coating according to claim 1, characterized in that: The rare earth element metal salts in the first electrolyte and the second electrolyte are two or more of yttrium nitrate, cerium nitrate, scandium nitrate, ytterbium nitrate, gadolinium nitrate and lanthanum nitrate.
6. The control method of the dendritic structure of the multi-principal rare earth doped zirconia thermal barrier coating according to claim 1, characterized in that: The conditions of the first electrolysis and the second electrolysis are: pulse voltage of 200-500V, operating frequency of 100-1000Hz, duty cycle of 5-30%, electrolysis temperature of 0-50°C, and time of 10-120min.
7. The control method of the dendritic structure of the multi-principal rare earth doped zirconia thermal barrier coating according to claim 1, characterized in that: The high temperature alloy specimens with bonding layer were prepared by the following process: The surface of the high-temperature alloy sample is sandblasted, and then a wide-range high-energy plasma spraying method is adopted to spray on the surface of the high-temperature alloy sample to form a bonding layer, thereby obtaining a high-temperature alloy sample with a bonding layer.
8. The method for controlling the dendritic structure of a multi-principal rare earth doped zirconia thermal barrier coating according to claim 1, characterized in that: The thickness of the adhesive layer is 50 to 150 μm.
9. The method for controlling the dendritic structure of a multi-principal rare earth doped zirconia thermal barrier coating according to claim 1, characterized in that: The bonding layer is made of NiCrAlY, NiCoCrAlY or CoNiCrAlY.
10. The method for controlling the dendritic structure of a multi-principal rare earth doped zirconia thermal barrier coating according to claim 1, characterized in that: The high temperature alloy specimen is an iron-based high temperature alloy, a nickel-based high temperature alloy or a cobalt-based high temperature alloy.
Citation Information
Patent Citations
Preparation method of thermal barrier coating on aluminum, magnesium alloys and their composites
CN102277606A
Method for preparing CeO2-Al2O3 compound ceramic layer by electrolytic deposition of cathode micro-arc plasma on surface of TiAl alloy
CN107557836A
Preparation method of aluminum oxide / ceramic lubricating phase thermal barrier antifriction coating
CN114016104A
Thermal barrier coating with multilayer structure on surface of magnesium alloy and preparation method of thermal barrier coating
CN117448815A
Method for electrolytic deposition of high-entropy rare earth zirconate thermal barrier coating
CN118256974A
Cited By
Titanium wire surface treatment process for manufacturing titanium alloy spectacle frame
CN121976274A